Us against you : a novel - Backman, Fredrik, 1981- (Beartown, 2018)
A small community tucked deep in the forest, Beartown is home to tough, hardworking people who don't expect life to be easy or fair. No matter how difficult times get, they've always been able to take pride in their local ice hockey team. So it's a cruel blow when they hear that Beartown ice hockey might soon be disbanded. What makes it worse is the obvious satisfaction that all the former Beartown players, who now play for a rival team in the neighboring town of Hed, take in that fact. As the tension mounts between the two adversaries, a newcomer arrives who gives Beartown hockey a surprising new coach and a chance at a comeback.